Adaptive compensators for perturbed positive infinite-dimensional systems - Curtain, Ruth F.; Demetriou, Michael A.; Ito, Kazufumi (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this investigation is to construct an adaptive observer and an adaptive compensator for a class of infinite-dimensional plants having a known exogenous input and a structured perturbation with an unknown constant parameter, such as the case of static output feedback with an unknown gain.
Keywords: infinite-dimensional systems; positive real systems; adaptive controllers